2021
DOI: 10.21107/agriekonomika.v10i1.10147
|View full text |Cite
|
Sign up to set email alerts
|

Determinant Factors for Cattle Insurance as a Risk Management Strategy

Abstract: Cattle farmers in Gunungkidul Regency face several cattle diseases such as Helminthiasis, Anthrax, Downer Cow Syndrome, and Intoxication in which these diseases mostly attack female cows. To prevent financial loss for the farmers, the government facilitates them with cattle insurance. This study aims to determine the reasons and the cattle farmers’ willingness-to-pay for the cattle insurance by conducting a survey addressed to 100 cattle farmers and identifying the factors related to it. This study used a Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Previous literature indicates that the age of farmers had a beneficial influence on their willingness to pay for livestock insurance in 15 investigations (Adjabui et al, 2019;Akintunde, 2015;Ali, 2013;Danso-Abbeam et al, 2014;Dong, Jimoh, Hou, & Hou, 2020;Ghazanfar, Wen, Abdullah, Ahmad, & Khan, 2015;Indra, Ula, & Nugroho, 2023;Jimoh Ibitoye, 2012;Kurniaty, Masyhuri, & Jamhari, 2021;Liu, Hou, Li, Min, & Mu, 2021;Manja, Chirwa, & Kambewa, 2015;Mensah et al, 2023;Musonda, 2012;Shang & Xiong, 2021;Teweldemedhin & Kafidi, 2009), while these 19 research revealed that older farmers were less likely to pay for livestock insurance, it was not clear why this was the case. (Abebe & Bogale, 2014;Aina et al, 2018;Amin, Abdullahi, Suryani, & Alias, 2014;Arshad et al, 2016;Dahal, Adhikari, & Khanal, 2022;Hill, Hoddinott, & Kumar, 2013;Kwadzo et al, 2013;Madaki et al, 2023;Mahboob, Rehman, Hamid, & Saeed, 2019;Mbonane & Makhura, 2018;Mutaqin & Usami, 2019;Nugrahaini, Masyhuri, & Suryantini, 2021;Oduniyi, Antwi, & Tekana, 2020;Ramasubramanian, 2012;Sadati et al, 2010;Sami, 2017;Singh, 2017;Sujarwo, 2017;Xiu, Xiu, & Bauer, 2012). These 8 studies found a negative effect of sex/gender on WTP for agriculture insurance " (Akintunde, 2015;…”
Section: Demographic and Socioeconomic Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous literature indicates that the age of farmers had a beneficial influence on their willingness to pay for livestock insurance in 15 investigations (Adjabui et al, 2019;Akintunde, 2015;Ali, 2013;Danso-Abbeam et al, 2014;Dong, Jimoh, Hou, & Hou, 2020;Ghazanfar, Wen, Abdullah, Ahmad, & Khan, 2015;Indra, Ula, & Nugroho, 2023;Jimoh Ibitoye, 2012;Kurniaty, Masyhuri, & Jamhari, 2021;Liu, Hou, Li, Min, & Mu, 2021;Manja, Chirwa, & Kambewa, 2015;Mensah et al, 2023;Musonda, 2012;Shang & Xiong, 2021;Teweldemedhin & Kafidi, 2009), while these 19 research revealed that older farmers were less likely to pay for livestock insurance, it was not clear why this was the case. (Abebe & Bogale, 2014;Aina et al, 2018;Amin, Abdullahi, Suryani, & Alias, 2014;Arshad et al, 2016;Dahal, Adhikari, & Khanal, 2022;Hill, Hoddinott, & Kumar, 2013;Kwadzo et al, 2013;Madaki et al, 2023;Mahboob, Rehman, Hamid, & Saeed, 2019;Mbonane & Makhura, 2018;Mutaqin & Usami, 2019;Nugrahaini, Masyhuri, & Suryantini, 2021;Oduniyi, Antwi, & Tekana, 2020;Ramasubramanian, 2012;Sadati et al, 2010;Sami, 2017;Singh, 2017;Sujarwo, 2017;Xiu, Xiu, & Bauer, 2012). These 8 studies found a negative effect of sex/gender on WTP for agriculture insurance " (Akintunde, 2015;…”
Section: Demographic and Socioeconomic Factorsmentioning
confidence: 99%
“…The more the chances to be willing to insure, the more educated the farmer is. Education positively influenced the propensity of farmers to pay for livestock insurance, according to these 23 studies " (Aina et al, 2018;Akintunde, 2015;Ali, 2013;Danso-Abbeam et al, 2014;Dong et al, 2020;Ellis, 2016;Ghazanfar et al, 2015;Gulseven, 2020;Indra et al, 2023;Jimoh Ibitoye, 2012;Kurniaty et al, 2021;Madaki et al, 2023;Manja et al, 2015;Mehmood, Ullah, e Ali, Baber, & Ashraf, 2022;Mohammed & Ortmann, 2005;Musonda, 2012;Mutaqin & Usami, 2019;Nugrahaini et al, 2021;O'Reilly, Bishu, Lahiff, & Gebregziabher, 2018;Sami, 2017;Singh, 2017;Suharyanto, Ansyor, & Hidayat, 2021;Sujarwo, 2017)" whereas 13 studies have demonstrated a negative correlation between education and farmers' "willingness to pay for livestock insurance (Adjabui et al, 2019;Arshad et al, 2016;Dahal et al, 2022;Khan, Chander, & Bardhan, 2013;Kwadzo et al, 2013;Mahboob et al, 2019;Mbonane & Makhura, 2018;Mensah et al, 2023;Nyaaba et al, 2019;Oduniyi et al, 2020;Shang & Xiong, 2021;Teweldemedhin & Kafidi, 2009;Xiu et al, 2012)". Sadati et al (2010) found a positive effect of literacy on the adoption of crop insurance.…”
Section: Demographic and Socioeconomic Factorsmentioning
confidence: 99%
See 3 more Smart Citations